UTILIZATION OF ISOLATED THERAPEUTIC BACTERIA IN TOPICAL OINTMENT FOR INFECTION TREATMENT - & et al., Alziadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study includes the using therapeutic bacteria isolate in topical ointment for bacterial vaginosis treatment and to compare it with metronidazole ointment that use in a clinical trial under medical supervision. Four active Lactobacillus probiotics bacteria were cultured in %12 skim milk , three of these bacteria were commercial types and one Iraqi local isolate , the total bacterial count of probiotics bacteria were around ≥ 1012 cfu/ml . %10 of individually culture free cells filtrate were added to Muller Hinton broth with secretions of patients infected with bacterial vaginosis "BV", %50 of natural organic components and %50 of local isolate Lactobacillus plantarum cultured in skim milk were mixed to prepare the natural ointment. Eighty-nine BV volunteers were divided into two group, first was 43 volunteers used probiotic ointment, the second group was 46 volunteers used metronidazole ointment "as control group", both groups were under medical observation for two weeks. The results shown that Iraqi local isolate Lb . plantarum gave best inhibition in vitro, according to Amsel criteria the rate of healing with Lb . plantarum ointment group was %97.87, it was higher than metronidazole ointment %91.30 and the healed cases numbers were increased at the day 7 and 14,it has been noticed that the results were positive based on vaginal secretions, and whiff test, clue cell and the pH was above 4.5 shown significant progress. According to Nugent criteria Lb . plantarum ointment gave higher healing percentage which was %95.35.